Oxygen Minimum Zone of the tropical North Atlantic - Cruise MSM22 - October 24, 2012 - November 23, 2012 - Mindelo (Cape Verde Islands) - Mindelo (Cape Verde Islands) ... - Brandt, Peter; Bittig, Henry; Didwischus, Sven-Helge; Fu, Yao; Funk, Andreas; Hahn, Johannes; Hauss, Helena; Herrford, Josefine; Kiko, Rainer; Kisjeloff, Boris; Kopte, Robert; Krahmann, Gerd; et al. (DFG-Senatskommission für Ozeanographie, 2014)
Cruise MSM22 is a joint effort of the Kiel Collaborative Research Centre SFB 754 ("Climate - Biogeochemistry Interactions in the Tropical Ocean") involving the BMBF joint projects NORDATLANTIK/RACE and SOPRAN as well as of the German-French-African Cooperative Project AWA. The main goal within the framework of the SFB 754 was the quantification of oxygen supply to the oxygen minimum zone (OMZ) of the Eastern Tropical North Atlantic (ETNA). Ventilation processes to be investigated include lateral and vertical mixing and oxygen advection (SP A3 and A4). The role of zooplankton for oxygen consumption and biogeochemical cycles (SP B8) was another focus of this cruise. All planned hydrographic and current data could be acquired as planned, including the successful recovery of all moorings with an overall very large data gain. The glider swarm experiment at the southern rim was performed as planned after deploying the mooring array. By the combined analysis of glider and mooring data (after mooring recovery in ... : MARIA S. MERIAN-Berichte ...